2011
DOI: 10.1111/j.1466-8238.2011.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Spurious thresholds in the relationship between species richness and vegetation cover

Abstract: Aim  Thresholds often exist in the relationship between species richness and the area of remaining habitat in human‐modified landscapes, prompting debate about the mechanisms responsible. We hypothesize that if species–area relationships differ with underlying factors such as landscape productivity, and such factors correlate with patterns of habitat clearance, then spurious thresholds can arise where the separate species–area relationships intersect. We assessed whether this phenomenon could explain landscape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 35 publications
4
56
0
1
Order By: Relevance
“…Understanding interspecific variation in species' responses to human disturbances is important to enable effective conservation decisionmaking, for example, by informing habitat protection and restoration targets to maintain important ecological phenomena such as species-area thresholds (Bruner et al 2001, Bleher et al 2006, Maron et al 2012, Game et al 2013. Protected areas are frequently viewed as safeguarding ecological communities (Bruner et al 2001); however, particularly in developing countries, where funds and national strategies for conservation and protected areas are low, protected areas frequently fail to adequately achieve this aim.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding interspecific variation in species' responses to human disturbances is important to enable effective conservation decisionmaking, for example, by informing habitat protection and restoration targets to maintain important ecological phenomena such as species-area thresholds (Bruner et al 2001, Bleher et al 2006, Maron et al 2012, Game et al 2013. Protected areas are frequently viewed as safeguarding ecological communities (Bruner et al 2001); however, particularly in developing countries, where funds and national strategies for conservation and protected areas are low, protected areas frequently fail to adequately achieve this aim.…”
Section: Introductionmentioning
confidence: 99%
“…Landscapes with more forest cover support a larger species pool (Hu et al 2012, Taylor et al 2012) through both sampling effects (Wiens 1992, Whittaker andFernández-Palacios 2007) and because a greater forest extent offers habitat diversity (Radford et al 2005, Maron et al 2012. Several empirical studies have shown that sites in landscapes with more forest support higher densities of reptiles (McAlpine et al 2015), greater species richness and abundance of birds (Villard et al 1999, Mortelliti et al 2010, Martensen et al 2012, Taylor et al 2012, and greater richness of small mammals (McAlpine et al 2006, Estavillo et al 2013).…”
Section: Extent Of Forest and Species Richnessmentioning
confidence: 99%
“…As habitat extent decreases, so do ecological functions and associated biodiversity in the landscape (Swift and Hannon 2010). Species richness may respond nonlinearly to habitat loss, and decline sharply when the extent of forest exceeds certain threshold levels (Maron et al 2012, Ochoa-Quintero et al 2015. For example, in the eastern Australia, Maron et al (2012) found a non-linear relationship between woodland birds and landscape-level forest extent.…”
Section: Extent Of Forest and Species Richnessmentioning
confidence: 99%
See 2 more Smart Citations